Institutional policies to attract international academics in Portugal in an adverse context - Carvalho, T.; Cardoso, S.; Diogo, S.; Sin, C.; Videira, P. (International faculty in Asia: In comparative global perspective, 2021)
The European Union’s (EU) decision to become ‘the most competitive and dynamic knowledge-based society in the world’ by 2000 included key policies such as the creation of a European Research Area (ERA) and a European Higher Education Area (EHEA) capable of attracting academics from other countries. Recruiting the best academics, and especially the best researchers, has become an issue of increasing importance in European higher education policy, with numerous studies reflecting the way these policies are translated at the national level. However, little is known about institutional policies to attract international academics. This is particularly challenging in countries that have faced severe economic crisis in the past years, as is the case of Portugal. This chapter introduces an overview of the situation of international academics in Portugal and analyses, based on a case study of two universities, the institutional policies that have been defined to recruit these academics. The analysis of qualitative data deriving from semi-structured interviews with key institutional decision-makers reveals that institutions experience difficulties in defining clear policies in this matter, although differences can be found between institutions.